Pengaruh Filler Partikel Serbuk Genting Limbah (PSGL) terhadap Mekanik dan Sifat Thermal Komposit Polyester-Serat Cantula - wanto, Sis; mal, Bas (ReTII, 2017)
Effect of precarious powder particles waste filler (PSGL) on mechanical properties and thermal properties of polyester-fiber composites cantula. This study aims to determine the effect of waste tile filler powder particles on Polyester-fiber composite on mechanical properties and thermal properties. Testing of mechanical properties of the composite is through by testing the impact strength (ASTM D 5941 standard), flexural strength test (ASTM D 790 standard ), and a Burn Rate test (ASTM D 635 standard). Tests to determine the thermal properties of the test conducted by FTIR, and SEM to determine the composite morphology. Polyester resin matrix composites using BQTN 157, reinforced by hibride using fiber cantula cut 10 cm and composed of random and precarious powder particles 100-120 mesh, as well as with MEKP hardener. Fiber cantula with a volume fraction of 40% mixed with precarious powder particles using Isopropyl Alcohol 5 wt%, mixing with a mixer for 10 minutes rotation of 100 rpm, variations precarious powder particles in the mix is 0, 2, 4, 6, and 8%. Mixture and then in a molding press using a machine press with pressing 28 kg / cm2 to holding time 20 hours. Composite then cut into specimens and soaking treatment for 300 hours with the soaking fluid: Sea Water and mineral Water + vinegar woter 40%. The results of the measurement data obtained that composite specimens reinforced cantula fiber and filler PSGL 0% have flexural properties and impact properties is higher than the composite reinforced cantula fiber and filer PSGL 2, 4, 6, and 8%. FTIR characteristics of composite specimens unchange reactions and changes between the untreated composites with composite soaking treatment. Keywords: Composite polyester, reinforcing hibride, vinyl silane coupling agent.